Transcriptional profiling by RNA sequencing of black pepper (Piper nigrum L.) roots infected by Fusarium solani f. sp. piperis - Moreira, Edith C. O. (2017)
Black pepper (Piper nigrum L.) is the most traded spice worldwide and therefore has great economic value. One of the major limitations of its production is yield losses in fields due to root rot, a disease caused by Fusarium solani f. sp. piperis. This soil-borne pathogen disseminates rapidly in tropical countries. Biotechnological breeding is often presented as an efficient tool to produce resistant pepper cultivars. An RNA-sequencing experiment was used to take a snapshot of the root transcriptome 60 days after infection by the pathogen. The mapping of 67 million SOLiD single-end reads to the Fusarium genome identified many fungal transcripts coding constitutive proteins and two proteins involved in virulence and conidial formation. The annotation of black pepper transcripts obtained by de novo assembly predicted three proteins restricted to this species. While these transcripts were upregulated in infected roots, the corresponding predicted proteins had no hit in databases. A global analysis of differentially expressed black pepper genes, using terms of gene ontology, has demonstrated an enrichment of genes involved in proteolysis, plastid degradation, cell-wall remodeling and secondary metabolism, consistent with toxicity and necrotrophic fungal interactions that force plants to collaborate at the metabolic level. Detailed descriptions of up- or downregulated genes associated with plant defense suggested several genes implied in the biosynthesis of isoprenoids, especially for an upregulated terpene synthase, a putative geranylgeranyl diphosphate synthase, and a downregulated brassinosteroid signaling component (BAK1). These results provide new clues for investigating further target genes and biotechnological approaches for breeding black pepper resistance to Fusarium.